Clinicopathologic and Molecular Characteristics of Gastrointestinal MiNENs - Yeo, Min-Kyung; Yoon, Nara; Bae, Go Eun (Frontiers in Oncology, 2021)
Background: A mixed neuroendocrine–non-neuroendocrine neoplasm (MiNEN) is a recently defined entity that comprises a neuroendocrine tumor (NEN) component and a non-neuroendocrine tumor (nNEN) component. As MiNEN is a recently defined entity, its molecular nature is not well known. Here, we evaluated the clinicopathologic and molecular characteristics of gastrointestinal (GI) MiNENs. Methods: We performed a genomic analysis of 31 samples from 12 GI MiNEN cases using next-generation sequencing. We examined the primary NEN and nNEN components, as well as the metastatic NENs and nNENs. The relationships between the clinical tumor features (component, location, and grade) and their molecular characteristics were examined. Results: The 12 MiNENs included in the study were found in the stomach (n=10), distal rectum (n=1), and anus (n=1). Primary MiNENs that had NENs as the major component showed a worse clinical outcome than those that had nNENs as the major component. All distant metastatic tumors originating from MiNENs were NENs. In addition, NENs generally carried 1.5 times more gene mutations and copy number variations than nNENs. The ATRX gene deletion and TP53 gene mutation were the most common variants in both components of GI MiNENs. Conclusions: We have revealed the detailed clinicopathologic and molecular findings with distinguishable alterations of GI MiNENs. To our knowledge, this is the first study to report the ATRX gene deletion in GI MiNENs. The molecular characteristics of GI MiNENs could provide clues to the pathogenic origin and progression of GI MiNENs.